Introduction and evaluation of a novel hybrid brattice for improved dust control in underground mining faces: A computational study - Kurnia, J.C. (China University of Mining and Technology, 2015)
Abstract A proper control and management of dust dispersion is essential to ensure safe and productive underground working environment. Brattice installation to direct the flow from main shaft to the mining face was found to be the most effective method to disperse dust particle away from the mining face. However, it limits the movement and disturbs the flexibility of the mining fleets and operators at the tunnel. This study proposes a hybrid brattice system - a combination of a physical brattice together with suitable and flexible directed and located air curtains - to mitigate dust dispersion from the mining face and reduce dust concentration to a safe level for the working operators. A validated three-dimensional computational fluid dynamic model utilizing Eulerian-Lagrangian approach is employed to track the dispersion of dust particle. Several possible hybrid brattice scenarios are evaluated with the objective to improve dust management in underground mine. The results suggest that implementation of hybrid brattice is beneficial for the mining operation: up to three times lower dust concentration is achieved as compared to that of the physical brattice without air curtain. Â© 2015 Published by Elsevier B.V. on behalf of China University of Mining & Technology.